2016
DOI: 10.1097/meg.0000000000000598
|View full text |Cite|
|
Sign up to set email alerts
|

Obstructive sleep apnea is associated with fatty liver index, the index of nonalcoholic fatty liver disease

Abstract: Our results suggest a positive association between the severity of OSA and NAFLD defined by an elevated FLI, which may serve as a good biomarker for detecting NAFLD in OSA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Agrawal [49] , 2015 (India) Chen [37] , 2016 Qi [50] , Trzepizur [39] , 2018 -AHI and ODI were the factors with the strongest independent association with LSM Bhatt [42] , 2019 -OSA and NAFLD operate as an independent contributors to the increased systemic inflammation that occurs in overweight/obese subjects ALT: Alanine aminotransferase; AHI: Apnea-hypopnea index; APRI: Aspartate aminotransferase to platelet ratio index; AST: Aspartate aminotransferase; BMI: Body mass index; CPAP: Continuous positive airway pressure; CT: Computed tomography; FLI: Fatty liver index; LSM: Liver stiffness measurement; NAFLD: Non-alcoholic fatty liver disease; ODI: Oxygen desaturation index; OSA: Obstructive sleep apnea; PSG: Polysomnography; SpO 2 : Oxygen saturation.…”
Section: Patient Characteristics Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Agrawal [49] , 2015 (India) Chen [37] , 2016 Qi [50] , Trzepizur [39] , 2018 -AHI and ODI were the factors with the strongest independent association with LSM Bhatt [42] , 2019 -OSA and NAFLD operate as an independent contributors to the increased systemic inflammation that occurs in overweight/obese subjects ALT: Alanine aminotransferase; AHI: Apnea-hypopnea index; APRI: Aspartate aminotransferase to platelet ratio index; AST: Aspartate aminotransferase; BMI: Body mass index; CPAP: Continuous positive airway pressure; CT: Computed tomography; FLI: Fatty liver index; LSM: Liver stiffness measurement; NAFLD: Non-alcoholic fatty liver disease; ODI: Oxygen desaturation index; OSA: Obstructive sleep apnea; PSG: Polysomnography; SpO 2 : Oxygen saturation.…”
Section: Patient Characteristics Resultsmentioning
confidence: 99%
“…Arisoy et al [41] observed that BMI and hepatosteatosis grade progressively and significantly increased from patients without OSA to those with severe OSA. Chen et al [37] found a positive association between the severity of OSA and NAFLD. In particular, the prevalence of NAFLD was 20.4% in patients with AHI < 15 whereas it reached 52.1% in patients with AHI ≥ 15.…”
Section: The Severity Of Nafld Is Associated With the Increase In Osamentioning
confidence: 98%
See 1 more Smart Citation
“…Many clinical scores like NAS and SAF (steatosis, activity and fibrosis) are used for the diagnosis of NAFLD [ 50 , 51 ]. Non-invasive tools like fatty liver index, serum algorithm and elastography for diagnosis of NASH have been recently validated [ 51 - 56 ]. The clinical significance of NASH is that it is associated with varying degrees of fibrosis, extremes of which can progress to cirrhosis and hepatocellular carcinoma [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A zsírindex hasznos biológiai jelzője a NAFLD súlyosságának OSA-betegekben. Alacsony fokozatú gyulladás, oxidatív stressz és ectopiás zsírlerakódás közös jellemzői a krónikus obstruktív tüdőbetegségnek (COPD) is, és hozzájárulnak a NAFLD kialakulásához [64]. Viglino és mtsai validált, noninvazív módszereket alkalmaztak a steatosis, a NASH és a májfibrosis vizsgálatára.…”
Section: Obstruktív Alvási Apnoe/hypoventilatiós Szindrómaunclassified